A cross-sectional study to assess diabetic risk using Indian diabetic risk score among the urban population of Perambalur, South India - M., Tamilarasan; Selvaraju, Maniprabhu; Kulothungan, Karthikeyan; T., Srirangathan (International Journal Of Community Medicine And Public Health, 2021)
Background: Various studies from the urban population shows people are more susceptible to develop type 2 diabetes mellitus. Since the cause of diabetes is multifactorial it is necessary to screen the population to identify high-risk individuals. The objective of the study was to estimate the risk of developing type 2 Diabetes Mellitus (T2DM) using the Indian diabetes risk score (IDRS) and its determinants in the urban field practicing area of the medical college in Perambalur district. Methods: A cross-sectional study was conducted in an urban field practicing area of Dhanalakshmi Srinivasan Medical College and Hospital in Perambalur district. 400 participants of age more than 20 years enrolled in this study. IDRS risk score and data on other risk factors were obtained for every individual. Data entry was done in Excel and statistical analysis was done with SPSS version 16. Results: In our study, the proportion of male and female were almost equal. One-third of the participants 124 (31%) had a high risk of developing type 2 diabetes mellitus. Similarly, half of them 188 (47%) were at moderate risk and 88 (22%) had a low risk for diabetes. Statistically, a significant association was seen between high risk for T2DM and increased age, positive family history, Low socioeconomic status, living as a nuclear family, habits of smoking/Alcohol, and sedentary lifestyle. Conclusions: The risk of developing type 2 diabetes mellitus among the urban population is rising trends. For effective screening of the general population, IDRS can be used.